Assessment of Belg 2022 Climate and Climate Outlook of the upcoming Kiremt 2022 - Teshome, Asaminew; Tesfaye, Kindie; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ethiopian Meteorological Institute has been generating seasonal climate outlook forum three times a year and provided to socioeconomic sectors. Those forecasts information are vital inputs to ensure and sustain the development of Ethiopia as the information is used to minimize risks due to weather and climate hazards and maximize positive impacts. Recently the Institute has implementing NFCS-E and started co-design and co-production of climate services with key socioeconomic sectors expected to strength the production, availability, delivery and application of science-based climate prediction and services in Ethiopia.